Effects of prenatal exposure to genistein on learning and memory function in Sprague Dawley rat offspring - Zulfiah, Mohamed, Moosa. (University of Pretoria, 2025)
Dissertation (MSc (Anatomy and Physiology))--University of Pretoria, 2025.